1994
DOI: 10.1007/bf00032464
|View full text |Cite
|
Sign up to set email alerts
|

Tearing resistance of multi-layer plastic films

Abstract: AbstracL The tear resistance of multi-layered plastic films can be generally predicted from the tear resistance of individual layers by an additive rule. The most notable exception from this additive rule is the case of multi-layered films containing a polyethylene layer. The reason for this specific case is explained by the constraint on the plastic yield zone of polyethylene, which causes a dramatic drop in the tear resistance of the multi-layered film. An extensive plastic zone is generated during the tear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Wu et al . found that laminating through LLDPE with other polymeric films could result in an anti‐synergistic effect, and the tear resistance became equal or less than that of LLDPE film alone . However, in this study, the multi‐layer film had only up to three layers, and the double sided adhesive tape was used as the binding layer.…”
Section: Introductionmentioning
confidence: 79%
“…Wu et al . found that laminating through LLDPE with other polymeric films could result in an anti‐synergistic effect, and the tear resistance became equal or less than that of LLDPE film alone . However, in this study, the multi‐layer film had only up to three layers, and the double sided adhesive tape was used as the binding layer.…”
Section: Introductionmentioning
confidence: 79%
“…trong đó τ ult là ứng suất cắt giới hạn của ni lông, (N/mm 2 ); A c là diện tích vùng cắt, (mm 2 ), phụ thuộc vào các thông số hình học của dao. [8][9][10] a. Xét cho trường hợp xé một lớp màng trong đó G là lực xé tạo ra trên một đơn vị chiều dày do lực F t , (N/m); ∆W là công của lực F t :…”
Section: Xây Dựng Mô Hình Tính Toán Các Thành Phần Lực Cản Trong Quá unclassified
“…5.62. Las investigaciones se han basado en un trabajo de Wu et al [150], en el que la restricción se conseguía por medio una banda adhesiva. En este sentido, el método todavía está en una fase de desarrollo experimental.…”
Section: Influencia De La Velocidad De Ensayounclassified